2020
DOI: 10.21203/rs.3.rs-22827/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and grade of RLS in migraine: a prospective study of 251 migraineurs by synchronous test of c-TTE and c-TCD

Abstract: Background RLS is considered as a risk factor for migraine, but the correlation between the RLS and migraine remains controversial. To investigate the prevalence and Right-to left shunt (RLS) grade of PFO in patients with migraine (including migraine with aura and without) and assess the association between PFO and migraine. Methods Synchronous test of contrast transthoracic echocardiography (c-TTE) and contrast transcranial Doppler ultrasonography (c-TCD) was conducted in 251 patients with migraine, includi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…This explains why it was difficult to detect shunts with c-TTE when c-TCD was a provoked shunt. Some scholars have proposed that the simultaneous execution of c-TCD and c-TTE can prevent errors caused by ineffective Valsalva maneuvers and improve the detection rate of c-TTE [ 18 ]. When the results of c-TCD and c-TTE were inconsistent, only one patient tested negative for c-TCD but positive for c-TTE.…”
Section: Discussionmentioning
confidence: 99%
“…This explains why it was difficult to detect shunts with c-TTE when c-TCD was a provoked shunt. Some scholars have proposed that the simultaneous execution of c-TCD and c-TTE can prevent errors caused by ineffective Valsalva maneuvers and improve the detection rate of c-TTE [ 18 ]. When the results of c-TCD and c-TTE were inconsistent, only one patient tested negative for c-TCD but positive for c-TTE.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the Valsalva maneuver, cTTE examination can be used to assess the closure of the foramen ovale by performing contrast imaging of the right heart, to observe whether any microbubbles enter the left atrium through the unclosed foramen ovale after the full opacification of right atrium. It can not only display the structure of the foramen ovale but also quantify RLS by observing the number of microbubbles in the left atrium [ 5 ]. However, whether the RLS result displayed by cTTE is related to the severity of migraine, as well as the value of cTTE in the follow-up of interventional occlusion needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…The application of transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) has greatly improved the accuracy of the diagnosis of PFO, but the sensitivity of RLS examination is relatively low. It has been confirmed that contrast transthoracic echocardiography (cTTE) can dynamically display the presence or absence of RLS in PFO in real-time, and can quantitatively assess the flow volume of RLS [ 5 ]. However, whether the RLS results displayed by cTTE are associated with the severity of migraine and its value in the follow-up of interventional occlusion needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that PFO is significantly correlated with migraine, especially migraine with aura. In a prospective study, Zhao et al described that the prevalence of large RLS, large-size PFO (≥2.0 mm), and permanent RLS in migraine patients with aura was higher than that in healthy controls [ 23 ]. Meanwhile, Tang et al [ 24 ] recently found that the prevalence of migraine without aura in the PFO group was significantly higher than that in the group without PFO, so PFO was also closely related to migraine without aura.…”
Section: Pfo and Migrainementioning
confidence: 99%